A Study on the Optimization of FDM Parameters for the Manufacturing of Compression Specimens from recycled ASA in the Context of the Transition to the Circular Economy - Zisopol, Dragos Gabriel; Minescu, Mihail; Iacob, Dragos Valentin (Engineering, Technology & Applied Science Research, 2025)
The present study investigates the optimization of the FDM parameters, that is, the height of the deposited layer in one pass (Lh) and the filling percentage (Id), for the manufacture of compression specimens from recycled ASA (rASA) in the context of transitioning to the circular economy. The Anycubic 4Max Pro 2.0 3D printer was utilized, where compression specimens were additively manufactured from rASA 45 using the following variable parameters: Lh = 0.10 mm, 0.15 mm, and 0.20 mm, and Id = 50%, 75%, and 100%. All compression specimens were tested on the Barrus White 20 kN universal testing machine. It was found that the Compressive strength (Cs) is influenced by the two considered variable parameters of the Fused Deposition Modeling (FDM), Lh and Id, but the overwhelmingly influencing parameter is Id. According to the results of the FDM parameter optimization for the manufacture of compression specimens from rASA, Lh = 0.10 mm and Id = 100%.